COMPARISON OF MICROSCOPIC AFB RESULTS WITH NaOH DECONTAMINATION VARIATIONS - Hartono Gumilar; Yusianti Silviani (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Bacteriological examination to confirm the presence of Mycobacterium tuberculosis or Acid-Fast Bacilli (AFB) in pulmonary tuberculosis refers to the smear examination of sputum samples. Direct microscopic examination of AFB in sputum has limitations, as the sample often contains a large amount of tissue and mucus, which reduces the likelihood of collecting a specimen containing Mycobacterium tuberculosis bacilli. Therefore, a decontamination process is performed by adding NaOH solution to liquefy the sputum, thus increasing the effectiveness of microscopic examination. Decontamination is carried out by adding NaOH solutions at different concentrations, namely 2% and 4%. This study aims to compare the results of AFB microscopic examination using the conventional method and the decontamination method with 2% and 4% NaOH concentrations. A total of 20 samples were used, with mucoid and purulent sputum consistency. Decontamination was performed with a sample-to-NaOH ratio of 1:1. This research is an experimental analytic study with a cross-sectional approach. The average number of positive AFB counts using the conventional (control) method was 19, while the average AFB count in samples decontaminated with 2% NaOH was 24, and the average count in samples decontaminated with 4% NaOH was 31. Statistical analysis using One-Way ANOVA yielded an F-value of 12.718 with a significance value (sig.) of <.001 (< 0.05), indicating a significant difference in the AFB counts per 100 fields of view between the samples treated with 2% and 4% NaOH decontamination. Based on the findings of this study, it can be concluded that the more effective NaOH concentration for sputum sample decontamination in microscopic AFB examination is 4%.